Sleep spindling and fluid intelligence across adolescent development: sex matters - Bódizs, Róbert; Gombos, Ferenc; Ujma, Péter P.; Kovács, Ilona (Frontiers in Human Neuroscience, 2014)
Evidence supports the intricate relationship between sleep electroencephalogram (EEG) spindling and cognitive abilities in children and adults. Although sleep EEG changes during adolescence index fundamental brain reorganization, a detailed analysis of sleep spindling and the spindle-intelligence relationship was not yet provided for adolescents. Therefore, adolescent development of sleep spindle oscillations were studied in a home polysomnographic study focusing on the effects of chronological age and developmentally acquired overall mental efficiency (fluid IQ) with sex as a potential modulating factor. Subjects were 24 healthy adolescents (12 males) with an age range of 15–22 years (mean: 18 years) and fluid IQ of 91-126 (mean: 104.12, Raven Progressive Matrices Test). Slow spindles (SSs) and fast spindles (FSs) were analyzed in 21 EEG derivations by using the individual adjustment method. A significant age-dependent increase in average FS density (r = .57; p = .005) was found. Moreover, fluid IQ correlated with FS density (r = .43; p = .04) and amplitude (r = .41; p = .049). The latter effects were entirely driven by particularly reliable FS-IQ correlations in females [r = .80 (p = .002) and r = .67 (p = .012), for density and amplitude, respectively]. Region-specific analyses revealed that these correlations peak in the fronto-central regions. The control of the age-dependence of FS measures and IQ scores did not considerably reduce the spindle-IQ correlations with respect to FS density. The only positive spindle-index of fluid IQ in males turned out to be the frequency of FSs (r = .60, p = .04). Increases in FS density during adolescence may index reshaped structural connectivity related to white matter maturation in the late developing human brain. The continued development over this age range of cognitive functions is indexed by specific measures of sleep spindling unravelling gender differences in adolescent brain maturation and perhaps cognitive strategy.